2022
DOI: 10.3390/pharmaceutics14081617
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Medical Devices for Autologous Regenerative Medicine: From Innovation to Clinical Validation

Abstract: Regenerative medicine, based on the use of autologous tissues and embryonic, stem or differentiated cells, is gaining growing interest. However, their preparation, in a manner compliant with good practices and health regulations, is a technical challenge. The aim of this manuscript is to present the design of reliable CE marked medical devices for the preparation of standardized platelet-rich plasma (PRP) and other autologous biologics intended for therapeutic uses. There are numerous PRP isolation processes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In recent years, numerous studies have shown the suitability of autologous biocompatible materials in regenerative medicine [6]. Among them, blood-derived products generally described as platelet concentrates (PCs) have been largely studied as useful therapeutic agents [7][8][9][10].…”
Section: The Importance Of Platelet Concentrates (Pcs) In Regenerativ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, numerous studies have shown the suitability of autologous biocompatible materials in regenerative medicine [6]. Among them, blood-derived products generally described as platelet concentrates (PCs) have been largely studied as useful therapeutic agents [7][8][9][10].…”
Section: The Importance Of Platelet Concentrates (Pcs) In Regenerativ...mentioning
confidence: 99%
“…1 PRP-platelet-rich plasma; 2 COMP-Cartilage Oligomeric Matrix Protein; 3 H-PRP-platelet-rich plasma obtained from healthy young males (age ranging from 23 to 33 years); 4 OA-PRP-platelet-rich plasma obtained from older male patients (age ranging from 62 to 85 years) who suffered from severe knee osteoarthritis (OA); 5 BMSCs-bone-marrow-derived stem cells; 6 ADSCs-adipose-derived stem cells; 7 LAA-L-ascorbic acid.…”
Section: Biomaterials Main Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering aims to replace, repair, or regenerate organs and tissues damaged by trauma, disease, or congenital malformations ( Sahakyants and Vacanti, 2020 ), such as deficiencies in skin, bone, nerves, and tendons ( Gomri et al, 2022 ), by creating living human structures. Due to recent developments in cell biology, biomaterials, and other subject areas, research on tissue engineering has made great strides.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering is currently one of the fastest growing fields in medical and dental science. By applying principles of tissue engineering, trauma or genetic defects of tissue including skin, nerve, tendon or bone can be regenerated ( Gomri et al, 2022 ). Tissue engineering generally consists of three basic components: suitable stem cells, scaffolds, and growth factors ( La Noce et al, 2014 ; Anitua et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%